Shifts in consumer behavior towards organic products: Theory-driven data analytics. (July 2021) - Taghikhah, Firouzeh; Voinov, Alexey; Shukla, Nagesh; Filatova, Tatiana
Abstract: Consumer behavior is key in shifts towards organic products. A diversity of factors influences consumer preferences, driving planned, impulsive, and unplanned purchasing decisions. We study choices among organic and conventional wine using an extensive survey among Australian consumers (N = 1003). We integrate five behavioral theories in the survey design, and use supervised and unsupervised machine learning algorithms for analysis. We quantify a gap between intention and behavior, and emphasize the importance of cognitive factors. Findings go beyond correlation to the causation of behavior when combining predictive prowess with explanatory power. Results reveal that affective factors and normative cues may prompt unplanned and spontaneous purchasing behavior, causing consumers to act against their beliefs. Graphical abstract: Image 1 Highlights: Emotions, habits, impulse, intentions, and behavior are shown to interact. Trust and price are most important to determine organic wine purchasing. Negative emotions are associated with higher spontaneous purchasing. Normative cues have a powerful impact on consumers' organic wine choices. Machine learning methods can provide insights into behavioral change.